2020
DOI: 10.1109/jsen.2019.2956782
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity Enhancement of Piezoelectric Transducers for Impedance-Based Damage Detection via a Negative Capacitance Interface

Abstract: Piezoelectric transducers are used in many applications due to electromechanical coupling, which allows mechanical and electrical quantities to be related. This principle is used in the development of structural damage detection techniques such as electromechanical impedance (EMI) commonly used in structural health monitoring (SHM), where structural health is monitored by measuring and analyzing the electrical impedance of a transducer. As a piezoelectric transducer is a primarily capacitive device, its reacta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The electromechanical impedance (EMI) technique based on piezoelectric ceramic wafers (PZT) is commonly used for structural health monitoring [4][5][6]. In this technique, piezoelectric sensors are pasted on the structure.…”
Section: Introductionmentioning
confidence: 99%
“…The electromechanical impedance (EMI) technique based on piezoelectric ceramic wafers (PZT) is commonly used for structural health monitoring [4][5][6]. In this technique, piezoelectric sensors are pasted on the structure.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers demonstrated that piezoelectric impedance measurements can be enhanced using circuitry elements such as inductive circuitries 4,11,20,28,29 and negative capacitance interfaces. [30][31][32] Both inductive and negative capacitance circuitries are advantageous for system dynamics optimization. The inductive circuitry provides additional resonant features in a small frequency range.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental results showed that the FRF curves with inductance circuits are more sensitive to structural damage. Budoya et al 30 proposed a method that can improve the sensitivity of structural damage detection using a negative capacitance interface. In addition, Kim and Wang 4 enriched an EMI dataset by adjusting the inductance values in the proposed adaptive piezoelectric circuitry for mathematical-model-based damage identification.…”
Section: Introductionmentioning
confidence: 99%